Efficacy and safety of glucagon‐like peptide‐1/glucagon receptor co‐agonist JNJ‐64565111 in individuals with type 2 diabetes mellitus and obesity: A randomized dose‐ranging study. Issue 2 (21st January 2021) - Di Prospero, Nicholas A.; Yee, Jaqueline; Frustaci, Mary E.; Samtani, Mahesh N.; Alba, Maria; Fleck, Penny
Summary: Weight loss has been shown to improve metabolic parameters and cardiovascular risk in people with type 2 diabetes mellitus (T2DM). This phase 2 study evaluated the safety and efficacy of JNJ‐64565111, a dual agonist of GLP‐1 and glucagon receptors, in individuals with T2DM and class II/III obesity. In this randomized, double‐blind study, participants with T2DM (HbA1c 6.5%‐9.5%), body mass index of 35 to 50 kg/m 2 and stable weight were randomly assigned (1:1:1:1) to placebo or JNJ‐64565111 (5.0 mg, 7.4 mg or 10.0 mg). The primary endpoint was percent change from baseline in body weight at week 12. Of 195 dosed participants, 144 (73.8%) completed treatment. At week 12, placebo‐subtracted body weight changes were −4.6%, −5.9% and −7.2% with JNJ‐64565111 5.0 mg, 7.4 mg and 10.0 mg, respectively. All JNJ‐64565111 doses were associated with no change in HbA1c and slight numerical elevation of fasting insulin. Numerical increases in fasting plasma glucose were observed with JNJ‐64565111 5.0 mg and 7.4 mg. Incidence of treatment‐emergent adverse events, especially nausea and vomiting, was higher with JNJ‐64565111 vs placebo. Overall, JNJ‐64565111 significantly reduced body weight in a dose‐dependent manner vs placebo but was associated with greater incidence of treatment‐emergent adverse events, no HbA1c reductions, and increased fasting plasma glucose and fasting insulin.